Cysticercosis Masquerading as Lipo–Dermoid - Sekar, Mridhula; Shanbhag, Nita Umesh; Sahana, N (Nepalese Journal of Ophthalmology, 2018)
Cysticercosis is caused by the larval stage of Taenia solium (Pork tape worm). Humans are the definitive hosts where the life cycle is completed and pig is the intermediate host. Incidence in India varies from 2-38% based on the consumption of pork, general hygiene and socio-economic status of the population. The parasite on reaching the small intestine encysts itself in various tissues. Most commonly Brain, Eyes, subcutaneous tissue. Intravitreal cyst is the commonest intra ocular presentation. Death of the parasite and release of the contents of the cyst causes an intense inflammatory reaction that can be devastating. We report the condition in a nine-year-old boy who presented with mild right upper lid swelling wherein cysticercus cellulosae cyst was found within the mass of the right lateral rectus muscle. It becomes important to report this case because of the unusual site of the cyst which masqueraded as a lipo-dermoid.